PERLINDUNGAN KONSUMEN TERHADAP PEMBELIAN SKINCARE PALSU MELALUI E-COMMERCE DI PONTIANAK - NIM. A1011211219, YOLANDA (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract The development of e-commerce has provided convenience for consumers in purchasing various products, including skincare products. However, this convenience has also led to an increase in the circulation of fake products, which can harm consumers both economically and health-wise. One of the common issues is the sale of fake skincare products through e-commerce platforms such as Shopee. Therefore, this study aims to analyze consumer protection measures against the purchase of counterfeit skincare products through e-commerce (Shopee) on the Allshop store and identify legal remedies available to consumers regarding the purchase of fake skincare products through e-commerce (Shopee) on the Allshop.This study employs an empirical juridical method with data collection techniques through interviews and questionnaires distributed to consumers who have experienced similar issues. The collected data is analyzed using a qualitative descriptive method to provide an overview of consumer protection realities in cases of fake skincare product purchases. This study also examines the applicable consumer protection regulations and Shopee's policies in handling consumer complaints related to fake products.The research findings indicate that Allshop, as a seller, has taken responsibility by implementing a refund policy for consumers who file complaints within a maximum period of seven (7) days after receiving the product, in accordance with Shopee's policy. From a legal perspective, there are two legal remedies available to consumers: preventive and repressive measures. Preventive measures include filing a complaint with Allshop first (negotiation), and if no resolution is reached, consumers can contact Shopee